การพัฒนาโฟมแก้วฉนวนความร้อนจากของเสียอุตสาหกรรม - กรกฎ ภวนะวิเชียร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research, the thermally insulating glass foam (TIGF) was developed by wet process. Glass powder, slag powder, soap used as foaming agent and sodium silicate used as deflocculant were selected. The parameters i.e. the solid content (glass and slag powders) and water ratio for slip preparation, drying (70-100oC) and firing (800-900oC) temperatures, firing rate (3 and 5oC/min), soaking time (0-30 min) and sodium silicate content (5-25 wt%) were evaluated. The slip was formed by pouring into a plastic mould in the dimension 12x12x1 inches. The samples were dried and fired within individual condition. Morphology (pore size, pore distribution and pore structure), bulk density, water absorption, compressive strength and thermal conductivity were investigated as a function of each parameter. The results showed that TIGF was successfully fabricated by wet process. The starting proportion of 85 wt% glass powder, 15 wt% slag powder was mixed with soap and sodium silicate at 23 and 15 wt%, respectively. The solid and water ratio was controlled constantly at 1.7:1. The insulating glass foam was dried and then fired at 70 and 725oC, respectively with firing rate at 5oC/min for non-soaking. It was found that the TIGF had cellular structure with the homogeneously distribution of macro-pore size at 0.43±0.04 mm and thin cell walls. The 0.310 g/cm3 of bulk density, 150 %water absorption, 1.0 MPa of compressive strength and 0.130 W/m•K of thermal conductivity were achieved. Moreover, average pore diameter and water absorption increased with increasing the sodium silicate content, firing temperature, firing rate and soaking time. On the other hand, the bulk density, compressive strength and thermal conductivity were decreased.